The Compliance of the South African Social Security System with the International Covenant on Economic, Social and Cultural Rights - Yvette Basson (Obiter, 2021)
The ratification of the International Covenant on Economic, Social and Cultural Rights by South Africa has resulted in the provisions thereof becoming binding on the South African legislature. The right to social security is entrenched in the ICESCR, which provides for the elements of a social security system that must be complied with by states. This article sets out what is required of states in terms of the right to social security in the ICESCR by way of crystallising the elements of a social security system. Thereafter, the South Africa social security system is compared to these elements to determine whether there is compliance with the right to social security in the ICESCR.